7+10f=-8+7f-9

Simple and best practice solution for 7+10f=-8+7f-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+10f=-8+7f-9 equation:


Simplifying
7 + 10f = -8 + 7f + -9

Reorder the terms:
7 + 10f = -8 + -9 + 7f

Combine like terms: -8 + -9 = -17
7 + 10f = -17 + 7f

Solving
7 + 10f = -17 + 7f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-7f' to each side of the equation.
7 + 10f + -7f = -17 + 7f + -7f

Combine like terms: 10f + -7f = 3f
7 + 3f = -17 + 7f + -7f

Combine like terms: 7f + -7f = 0
7 + 3f = -17 + 0
7 + 3f = -17

Add '-7' to each side of the equation.
7 + -7 + 3f = -17 + -7

Combine like terms: 7 + -7 = 0
0 + 3f = -17 + -7
3f = -17 + -7

Combine like terms: -17 + -7 = -24
3f = -24

Divide each side by '3'.
f = -8

Simplifying
f = -8

See similar equations:

| (9x+8)=(8x+7) | | m=2/3b=-14 | | 3(3+y)2y=12 | | y=-0.8*25+72 | | 4+8h=9h | | 14x^2-88x+192=0 | | (10x+9)=(9x+8) | | 4y+10=6y-10 | | .51m+.03=.4m-.74 | | 2x+13+10=145 | | 11.64=1.2x+3 | | 6.4(5+3)=8 | | 10-4v=-5v | | 1.2y-0.1=0.2 | | 23x+-1+45=135 | | -16t^2+32x+20=h(t) | | 4k^2-62k+30=0 | | -1+45+23=135 | | 4.4=4(k+3) | | 10(1)+10y=15 | | f(0)=3x^2+2x-4 | | a^7=5 | | m=1/2b=-19 | | 15y+40=348 | | 30v^2+88v-6=0 | | 2x+125+163=38 | | h(x)=x^2-5x-36/x^2-81 | | 530.66=3.1 | | -7=-5y+4(-y+9)-7(7-3y) | | 3.2(m-1)=8 | | 4g^2-11g+6=0 | | -11x=8x+-6 |

Equations solver categories